STRATEGI PEMASARAN SARANG BURUNG WALET DI LAMONGAN MELALUI KARAKTERISTIK KERJA - Mellyta Wandha Chayaning; Isa Anshori (Jurnal Bisnis Terapan, 2022)
The management is changing quite radically, which is the change from a traditional model to a Total Quality Management (TQM) or what is often referred to as a management strategy. A strategy like this could demand an advantage in the matter speed, agility, learning, and employee competence. The study is an evaluation of implementing a management strategy carried out by owners of businesses swallow’s nest (Collacalia sp) in the Lamongan to enhance employee empowerment to create good job perception. Research on this swifts’ nest factory,according to the measurement of how the employees performance is focused on the work characteristics, includes the agility of an employee in cleaning the swallow’s nest it self, and maintrining the quality of the swallow’s nest which will eventually be sent out of the city for people to eat. The results of this study conclude that according to the measuring of how imployees performance on indicators for knowing how and what work is assessed both by them selves and by co workers. For the indicators it is a joint operation of inter-section employees, as well as between employees and above.